Labour Leader : a weekly journal of Socialism, Trade-Unionism & Politics. - Independent Labour Party (ILP) (Manchester : National Labour Press, 1913)
Bibliotheek Camille Huysmans
The official organ of the Independent Labour PartyPeriodiciteit: wekelijksRedactie: Ph. Snowden, J. Bruce GlasierBeheer: Blackfriars Street 30, ManchesterDrukker/Drukkerij: National Labour Press, Blackfriars Street 30, Manchester
Engels
Krant
Keywords: socialistische pers; Groot-Brittannië.